An investigation of the validity of a section of a theoretical model to predict work physiology parameters from age and weight : a research project presented in partial fulfilment of the requirements for the degree of Master of Business Studies at Massey University - Jeffrey, Glyn (Massey University, 1984)
Work physiology is the study of physiological parameters of the body during work. Two of these physiological parameters are commonly measured to assess the cost of work : oxygen consumption and heart rate. In 1979 a theoretical model was developed to estimate some ergonomic parameters from age, height and weight. While this model predicted anthropometric, biomechanical and work physiology parameters, the present research was concerned only with the section of the model predicting work physiology parameters of oxygen consumption and heart rate from age and weight. In this study oxygen consumption and heart rate values were obtained from measurement of seven subjects working on an ergometer. These values were then used to test three of the equations in the predictive model. Two of the equations were found to be unreliable as predictors of oxygen consumption and heart rate for this sample, while one of the equations was found to be reliable. Further research with a larger sample is necessary before any firm conclusions about this section of the model may be made.
Keywords: Physiological aspects; Work; Work measurement